HYGIENIC ASSESSMENT OF SCHOOL FURNITURE IN PRIMARY CLASSROOMS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study examined the provision of primary classrooms of schools with basic schoolchildren’s furniture, such as desks, chairs and blackboards, and also gave a hygienic assessment of the organization of schoolchildren’s workplaces. As a result of the study, the main shortcomings of school furniture and various parameters in organizing workplaces for primary schoolchildren were identified.